Overview of the structure, side effects, and activity assays of l-asparaginase as a therapy drug of acute lymphoblastic leukemia. Issue 2 (26th January 2022) - Wang, Nanxiang; Ji, Wenhui; Wang, Lan; Wu, Wanxia; Zhang, Wei; Wu, Qiong; Du, Wei; Bai, Hua; Peng, Bo; Ma, Bo; Li, Lin
Abstract : We summarized its structure and mechanism in detail, reviewed the detection approaches, and prospected the development of future detection assays. Abstract : l -Asparaginase (l -ASNase is the abbreviation, l -asparagine aminohydrolase, E.C.3.5.1.1) is an enzyme that is clinically employed as an antitumor agent for the treatment of acute lymphoblastic leukemia (ALL). Although l -ASNase is known to deplete l -asparagine (l -Asn), causing cytotoxicity in leukemia cells, the specific molecular signaling pathways are not well defined. Because of the deficiencies in the production and administration of current formulations, the l -ASNase agent in clinical use is still associated with serious side effects, so controlling its dose and activity monitoring during therapy is crucial for improving the treatment success rate. Accordingly, it is urgent to summarize and develop effective analytical methods to detect l -ASNase activity in treatment. However, current reports on these detection methods are fragmented and also have not been systematically summarized and classified, thereby not only delaying the investigations of specific molecular mechanisms, but also hindering the development of novel detection methods. Herein, in this review, we provided a detailed summary of the l -ASNase structures, antitumor mechanism and side effects, and current detection approaches, such as fluorescence assays, colorimetric assays, spectroscopic assays and some other assays. All of them possess unique advantages and disadvantages, so it has been difficult to establish clear criteria for clinical application. We hope that this review will be of some value in promoting the development of l -ASNase activity detection methods.